Review of patient safety target implementation in the dental clinic, semarang City - Aulia Nastiti Darajati; Kusuma Arbianti; Moh. Husnun Niam (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: WHO (World Health Organization) reported in 2004 the prevalence of KTD (adverse event) was 3.2-16.6% from studies in various countries. To minimize adverse event (KTD), WHO realizes this through the sixth goal of patient safety. Indonesia has also implemented the sixth goals of patient safety by issuing 2 health ministerial regulations number 1691/MENKES/PER/8/2011 concerning hospital patient safety. In addition to hospitals, health facilities such as dental clinics. Method: The research design used in this study was an observational study with a case study approach with a total of 142 research subjects. The research subjects included dentists and assistants at every dental clinic in Semarang City. The study was conducted by filling out a questionnaire consisting of 6 sections covering 6 patient safety. The data obtained were analyzed quantitatively by presenting the answers for each dimension and drawing conclusionsResult: The results obtained all data related to the implementation of 6 patient safety goals by dentists and dental assistants at the Semarang City Clinic. At each point patient safety goals get different implementation resultsConclusion: The conclusion is the value of applying 6 patient safety goals in order of highest to lowest results, namely the reduction of the risk of infection is very good, the increase in drug safety that needs to be watched out for is very good, the accuracy of patient identification is very good, the increase in effective communication is very good, the certainty of the exact location is good and the risk reduction The patient fell quite well